Síntese e caracterização de novos materiais luminescentes para detecção de radiação - Lima, Héstia Raíssa Batista Reis (2017)
This work aims the production of luminescent materials based on MgB4O7 (MBO) and Li2B4O7 (LBO), doped and undoped, by alternative routes, verifying the influence of the route on the optical properties and grain size. Sol-gel protein (SGP) and Pechini (MP) methods were chosen for the production of the samples. Structural characterization of the materials was performed through thermal measurements and X-ray diffraction (XRD). Thermal analyses indicate that the crystallization process of the samples at intervals of 700 to 1000 C for MBO and 500 to 700 C for LBO by both production methods. XRD measurements confirm the formation of single crystalline phase under synthesis conditions 900 C/2h (SGP) and 800 C/2h (MP) for MBO crystal and 650 C/2h (SGP) and 600 C/2h (MP) for MBO. These conditions also were used to doped samples but single phases for doped LBO cannot be obtained. All samples present a coloration that could disrupt the luminescent signal during thermoluminescence (TL) and optically stimulated luminescence (OSL) readings. Samples were washed with hydrogen peroxide aiming to test the influence of coloration in optical properties. Optical measurements showed that the samples no washed with hydrogen peroxide have more efficient TL signal than washed samples. As a rule, the unwashed samples of MBO:Ce,Li produced by both methods showed the best TL signal. The MBO:Dy,Li – SGP – washed samples showed only 10% of the batch discharge units 20 tablets with homogeneity tests. On the other hand, for both MBO:Dy,Li (SGP,MP) were verified that the TL signal decays with the decrease of the grain size and occurs a displacement of the position of the TL peaks. The minimum detectable dose calculated for the washed samples of the MBO:Ce,Li and MBO:Dy,Li were 0.02 Gy and approximately 0.3 Gy respectively for both production methods. The OSL measurements showed MBO:Dy,Li – SGP have the best signal and that grain size have no influence in OSL signal. Phototransferred thermoluminescence effect (PTTE) occurred to MBO:Dy,Li – washed samples. Photoluminescent (PL) measurements indicate high symmetry in the dopant region for the MBO:Ce,Li – MP - washed sample. The LBO samples produced by both methods presented high sensitivity to the production method, precursor reagents used and dopants.